THE EFFECTIVENESS OF TEACHING MATERIALS FOR WRITING DESCRIPTIVE TEXTS THROUGH FISHBONE DIAGRAM - Sandika Lumban Batu; Charlina; Hasnah Faizah (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to determine the effectiveness level of teaching module in writing descriptive texts for a junior high school level. This research utilized research and development (R and D) method proposed by Sugiyono. This study was conducted in ten steps including: (1) Potentials and problems, (2) Data collection, (3) Product design, (4) design validation, (5) design revision, (6) product trial, (7) product revision, (8) use trial, (9) product revision, and (10) mass production. The subjects in this study were 34 students at grade VIII SMP Negeri 6 Dumai. The data were gathered by conducting an interview and distributing questionnaires. Sources of data were the results of interviews, questionnaires, and literature studies. Then, data in this study were analyzed by using a Likert scale. Based on the results of this study, it could be concluded that Dumai Kotaku teaching module was effective to be used as teaching material for junior high school students. It was seen from the results of the validation assessment by lecturers and teachers, as well as the assessment by students. Moreover, the results of limited trials for students revealed that the final score was in very good category. Lastly, the student assessments and the results of limited trials to students showed a correlated result.